Analysis of the Corneal Anterior and Posterior Surface in Patients With Peripheral Hypertrophic Subepithelial Corneal Opacification. Issue 2 (March 2020) - Riedl, Jana C.; Musayeva, Aytan; Wasielica-Poslednik, Joanna; Weyer-Elberich, Veronika; Pfeiffer, Norbert; Gericke, Adrian
Abstract : Purpose: To characterize the corneal changes in peripheral hypertrophic subepithelial corneal opacification (PHSCO) considering elevation of the anterior and posterior corneal surface, corneal astigmatism, tear secretion, and endothelial cell density. Methods: Thirty-eight eyes of 22 patients with PHSCO on at least 1 eye and 38 eyes of 22 age- and sex-matched healthy subjects were included in this retrospective cross-sectional study. Using the Pentacam system (Oculus, Wetzlar, Germany), measurement of the anterior and posterior corneal surface was performed. In addition, the Schirmer test was conducted, and endothelial cells were counted in the central cornea with a specular microscope (SP-3000P; Topcon, Tokyo, Japan). Results: The mean age was 55.2±11.7 years in patients with PHSCO and 54.1±12.4 years in healthy subjects. The corneas of patients with PHSCO showed higher corneal astigmatism of both the corneal anterior and posterior surface (2.9/0.5 vs. 0.8/0.3 D, PHSCO vs. controls, P =<0.001/<0.01). The cornea was thickest in the peripheral 12-o'clock position and the peripheral superior nasal area. Remarkably, central endothelial cell density was markedly reduced in patients with PHSCO (2, 372.6 cell/mm 2 ±328.1 vs. 2, 673 cells/mm 2 ±287.6, P <0.01, PHSCO vs. controls). Also, the Schirmer test revealed lower tear secretion in patients with PHSCO (9.8±4.4 mm vs. 14.3±5.7 mm, P <0.001, PHSCO vs. controls). Conclusion: The astigmatism of both the anterior and posterior corneal surface is increased in patients with PHSCO. Intriguingly, tear secretion and central endothelial cell density are reduced in patients with PHSCO. These measurements may become useful to assess the impact of morphological changes on vision and to track disease progression in PHSCO.